2021
DOI: 10.1016/j.puhe.2021.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Differences in health literacy level of patients from public and private hospitals: a cross-sectional study in Turkey

Abstract: Objectives Policy-making based on a health literacy approach makes it a priority to develop people-centered public health strategies and programs, particularly in the time of COVID-19 across the world. This is the first study to assess health literacy levels of patients visiting public and private hospitals in Turkey and also compares these levels with sociodemographic and health-related variables by hospital type to suggest health policies aimed at improving the health literacy skills for patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…While not limited to pregnant women, many studies reported that the level of health literacy on COVID-19 was not only a cause of increased mental disorders, but also increased future anxiety 26 , 27 . Therefore, health literacy-based policy decisions and the provision of information as well as accurate knowledge and appropriate actions against novel infectious diseases are important 28 , 29 . However, the situation for pregnant women is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…While not limited to pregnant women, many studies reported that the level of health literacy on COVID-19 was not only a cause of increased mental disorders, but also increased future anxiety 26 , 27 . Therefore, health literacy-based policy decisions and the provision of information as well as accurate knowledge and appropriate actions against novel infectious diseases are important 28 , 29 . However, the situation for pregnant women is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…In the face of widespread low population health literacy, the ability of health professionals to proactively identify people with low health literacy and to tailor their communication to patients with different levels of health literacy is particularly important. As further research on health literacy is conducted, the understanding of health literacy is not restricted to the characteristics of individuals (Durmuş, 2021) but covers multifaceted factors that contribute to health literacy, including the people who provide health knowledge and the health service providers. The health literacy of each individual is influenced by multiple socio‐demographic elements, for example, educational level, life history and so on, which requires medical specialists to first assess the health literacy of patients and develop individualized health guidance programmes in order to help patients achieve better health outcomes.…”
Section: Introductionmentioning
confidence: 99%